Os efeitos da educação aprimorada, realizada por enfermeiros na qualidade do preparo intestinal para colonoscopia - Arslanca, Gamze (2022)
Objective: to evaluate the effect of nurse-performed enhanced patient education sessions on adequate bowel preparation and cecal intubation rates. Method: a prospective, quasi-experimental, comparative study with a quantitative approach. The intervention group (n=150) received education enhanced by a visual presentation and reminder calls. The control group (n=156) received the clinic’s standard written instructions. Adequate bowel preparation rates and other colonoscopy quality indicators were compared between the groups. Results: Boston Bowel Preparation scale scores and adequate bowel preparation rates were higher in the intervention group than in the control group (respectively, 6.76±2.1 vs. 5.56±2.4, p=0.000, and 80% vs. 69.2%, p=0.031). The cecal intubation rates were higher in the intervention group (80% vs. 67.3%, p=0.012). Due to inadequate bowel preparation, unsuccessful cecal intubation rates were 0% in the intervention group and 17.6% in the control group. Biopsy rates were higher in the intervention group (28% vs. 13.3%, p=0.002). Conclusion: the nurse-performed enhanced patient education sessions increase adequate bowel preparation rates and, in parallel, cecal intubation rates. To reach the colonoscopy quality standards recommended in the guidelines, it is suggested that patient education be supported by different training tools and given by health professionals.